Coaxial α-MnSe@N-doped carbon double nanotubes as superior anode materials in Li/Na-ion half/full batteries. Issue 32 (2nd August 2018) - Liu, Dai-Huo; Li, Wen-Hao; Liang, Hao-Jie; Lü, Hong-Yan; Guo, Jin-Zhi; Wang, Jiawei; Wu, Xing-Long
Abstract : One-dimensional coaxial double nanotubes consisting of α-MnSe inner tubes and N-doped carbon outer tubes were prepared as anode materials for Li-ion and Na-ion batteries. Abstract : Coaxial nanotubes are a significant class of nanoscale building blocks for advanced electrodes of secondary batteries. Herein, one-dimensional (1D) coaxial double nanotubes (DNTs) consisting of α-MnSe inner tubes and N-doped carbon (N–C) outer tubes (abbreviated as α-MnSe@N–C DNTs) are successfully prepared and are demonstrated to be promising anode material for Li-ion and Na-ion batteries (LIBs/NIBs). When used in LIBs, it was revealed by ex situ XRD/HRTEM studies and electrode kinetics that a new electrochemical α → β phase transition plays a crucial role in improving the cycling stability. As a result, the α-MnSe@N–C DNTs electrode delivers a high Li-storage capacity (800 mA h g −1 at 50 mA g −1 ), excellent rate capability (405 mA h g −1 at 14 A g −1 ) and ultra-long cycling stability (a high capacity retention of 87.2% even after 9000 cycles at 2 A g −1 ) with retained 1D morphology. In addition, the outer N–C nanotube can effectively protect the active α-MnSe inner nanotube to realize such outstanding electrochemical properties owing to the high electrical conductivity and particular 1D coaxial nanoarchitecture of the inner nanotube. Moreover, α-MnSe@N–C DNTs also exhibit excellent Li/Na-storage properties and full-cell performances when coupled with commercial LiFePO4 and LiNi0.6 Co0.2 Mn0.2 O2 cathodes in LIBs as well as with the Na3 V2 (PO4 )2 O2 F cathode in NIBs.